Characteristics of human potentiality and organizational behavior among IT users in Poland. An exploratory study - Kowal, Jolanta; Keplinger, Alicja (Charakterystyka potencjału ludzkiego i zachowań organizacyjnych wśród użytkowników IT w Polsce. Studium eksploracyjne, 2015)
The paper concerns the model of aspects of ethical competencies of human capital development in information systems in a transition economy, on the Polish labor market. The purpose of the research is to verify the association of Human Potentiality (HP) and Organizational Citizenship Behavior (OCB) among 263 IT users in relation to their professional position, in Poland. The authors used two new questionnaires in Polish studies: the Human Potentiality Inventory in achieving career goals (HPI) and an adapted Employee Behavior Questionnaire (EBQ). The authors estimated the levels of HP and the manifestation of OCB of IT users in relation to their professional position. Applying and popularizing the ideas of HP and OCB may have an effect on the development of staff’s ethical attitudes on the labor market, which increases commitment, efficiency and leads to economic growth. The research results complement the gap in the scientific literature that concerns the psychosocial characteristics of IT users such as Human Potentiality and sensitivity intelligence in terms of achieving career goals and ethical attitudes. The results show differences between bosses and subordinates and dependencies between the components of HP and OCB. The analysis is based on a random interpersonal network and sequence sampling with the passive optimal experiment design conducted among IT users for the first time in such a context in the Lower Silesia voivodship in Poland
Ekonometria = Econometrics, 2015, Nr 3 (49), s. 98-114
Keywords: Organizational Citizenship Behavior (OCB); Human Potentiality; IT users; model of aspects of ethical competencies; organizacyjne zachowania obywatelskie; potencjał jednostki; użytkownicy IT